Emergence of Fusarium incarnatum and Fusarium avenaceum in wilt affected solanaceous crops of the Northern Himalayas - Tasmeen J. Parihar; Madeeha Naik; Shafqat Mehraj; Syed Inam ul Haq; Maqsooda Perveen; Ishfaq Ahmed Malla; Taniya Abid; Nadia Gul; Khalid Z. Masoodi (Scientific Reports)
Abstract The objective of this study was to identify and characterize the fungal pathogens responsible for wilt diseases in solanaceous crops, specifically tomato, brinjal, and chili, in the Kashmir valley. Through both morphological and molecular analyses, including DNA barcoding of the ITS, TEF, RPB1, and RPB2 genomic regions, Fusarium incarnatum and Fusarium avenaceum were identified as the primary causal agents of wilt in tomato and brinjal, and chili, respectively. Pathogenicity tests confirmed the virulence of these pathogens, with typical wilt symptoms observed upon inoculation. This represents the first report of F. incarnatum and F. avenaceum as wilt pathogens in solanaceous crops in India. Phylogenetic analysis further confirmed the genetic variability of these pathogens, revealing their expanding host range. The findings underscore the growing adaptability of these Fusarium species to diverse agricultural systems and highlight the urgent need for targeted disease management strategies to mitigate the significant yield losses caused by Fusarium wilt in solanaceous vegetable production.